INITIAL PUBLIC OFFERING (IPO) - GLOBAL POSITIONING OF SHARES - Ergashev Javakhir son of Bakhodir (American Journals, 2023)
This article provides an overview of the global positioning of shares in the context of Initial public offering (IPO). An IPO is a process in which a privately held company offers its shares to the public for the first time. The global positioning of shares refers to the strategic factors and decisions associated with determining the availability of the offer and reaching out to investors around the world. In this annotation, we will study how companies approach the global positioning of shares during the IPO period. These include factors such as the selection of international markets for registration of shares, the assessment of demand for investors from different regions, the establishment of a different shareholder base. Companies may choose to list their shares on multiple stock exchanges to maximize access to global capital and increase visibility in the international investment landscape. Through this, they aim to attract a wide range of investors and increase their marketability. When choosing a Global position, various factors such as market conditions, regulatory requirements, investor preferences, strategic goals of the company are also taken into account. An in-depth analysis of these factors will help determine the optimal placement of shares in various global markets. In addition, the global positioning of shares through IPO can increase the company's reputation and trust, as a successful offer can express confidence and competence to investors around the world.
Keywords: IPO, investor, innovative technologies, antiterrorism activities, auction. An IPO is an initial public offering. In IPO, a private company lists its shares on the stock exchange and makes them available for purchase by the general public.